TECHNOLOGY FOR THE DEVELOPMENT OF STRENGTH ENDURANCE OF WRESTLERS BASED ON THE USE OF SPECIAL SIMULATORS AND EXERCISES IN FREESTYLE WRESTLING, TAKING INTO ACCOUNT AND MONITORING THE TRAINING LOADS OF WRESTLERS - Murodov Kamoliddin Nuritdinovich (Galaxy International Interdisciplinary Research Journal, 2021)
In job is presents the technology for the development of wrestlers’ strength endurance based on the use of special simulators and exercises in freestyle wrestling.